(untitled) (Economics and region, 2023)
Current instruments of strategic planning in the system of ensuring sustainable development of territorial communities are analyzed. The place of strategic planning in the socio-economic activity of economic entities is determined. Strategic planning instruments are systematized, in particular by stages of strategic planning (strategic analysis, strategic vision, strategy development, determination of the mechanisms of implementation of the chosen strategy, determination of criteria for the effectiveness of the implemented strategy). For each stage effective strategic planning instruments are provided, and the main goals and areas of application of each of the instruments are defined. The most of the strategic planning instruments were previously used mainly in the economic activities of economic entities, however, modern challenges require expanding the scope of their application for planning the activities of territorial communities. It is noted that strategic planning has a double meaning and at the same time is a separate economic process and an instrument of socio-economic activity of territorial communities. The main principles of strategic planning (consistency, complexity, effectiveness, transparency, measurability of goals, realism) are highlighted as the conditions for strategic planning to have the greatest positive effect on the sustainable development of territorial communities. Indicators of socio-economic activity of territorial communities at different levels (local, sectoral, regional, national level) are given. A study of foreign experience of strategic management in comparison with the current level of development of domestic territorial communities was conducted. It was determined that in Ukraine insufficient attention was paid to the commercial aspects of the activity of territorial communities, while abroad, and in particular in Poland, in the process of strategic planning, economic indicators of community activity (competitiveness, etc.) are taken into account equally with social ones, which ensures autonomous development of territories and increasing efficiency in the use of strategic planning instruments for sustainable development.